Long Term Effects of Major Macroeconomic Variables on the Brazilian Stock Market: A nonlinear ARDL application - MELO, MARCELO; GOMES, WELIGTON (Archives of Business Research, 2021)
This research used NARDL methodology to investigate relevant macroeconomic variables influence on the Brazilian stock market index. We used monthly data from January/2000 to July/2020 and the six macroeconomic variables investigated are described as follows: net government's debt/GDP (DEBT), exports (EXPORT), consumer confidence (ICC), liquidity ratio (M4_PIB), interest rate (SELIC) besides the stock market index (IBOV). All monthly data were collected from IPEADATA. The main conclusions are that there is long run effect of IBOVESPA due to a decrease of government debt is clear and statistically significant, the long run effect in the liquidity ratio also affects IBOVESPA index. Moreover, the most outstanding result was the long run effect of decrease in the interest rate over the IBOVESPA index. Sustainable reductions in the interest rate would consistently stimulate the stock market index. Research outcomes also indicate that long run asymmetries of government debt, liquidity ratio and interest rate are reliable and statistically significant.